Single sport specialization in youth sports: A survey of 3,090 high school, collegiate, and professional athletes - Buckley, P. S.; Bishop, M.; Kane, P.; Ciccotti, M. C.; Selverian, S.; Exume, D.; Emper, W. D.; Freedman, K. B.; Hammoud, S.; Cohen, S. B.; Ciccotti, M. B. (Annual Conference of the American Orthopaedic Society for Sports Medicine, 20-23 July 2017, 2017)
Objectives: Youth participation in organized sports in the United States is rising, with many athletes focusing on a single sport at an increasingly younger age. There is considerable debate regarding the rationale, optimal timing, injury risk, and the psychosocial health of a young athlete specializing early in a single sport. The purpose of our study was to compare youth single sport specialization in high school (HS), collegiate, and professional athletes with respect to the age of specialization, the number of months per year of single sport training, and injury attributed by the athlete to specialization. Methods: A survey was distributed to HS, collegiate and professional athletes prior to their yearly preparticipation physical exam. Demographic information, details of current sport commitment, and future athletic plans were collected. Athletes were asked if they had chosen to specialize in only one sport during their childhood/adolescence, and data was then collected pertaining to when, how, and why this decision was made. Continuous da a was analyzed using one-way ANOVA analysis and categorical variables were compared using chi-square analysis. Results: A total of 3,090 athletes d the survey (503 HS, 856 collegiate, and 1,731 professional athletes). 46.3% of HS athletes, 67.7% of collegiate athletes, and 45.9% of professional athletes specialized to play a single sport during their childhood/adolescence (p< 0.00001). Single sport specialization in these groups occurred at a younger age in the HS athletes (12.7 ± 2.4 years old), compared to the college (14.8± 2.5 ears old) and professional athletes (14.06 ± 2.8 years old) (p<0.001). At the age of specialization, collegiate athletes spent more months per year training for their sport (10.03 ± 2.64 months), compared to HS (8.5 ± 3.4 months) and professional athletes (8.3 ± 3.5 months) (p<0.0001). A lower percentage of professional athletes believed that specialization helped them to play at a higher level (61.7%) compared to HS (79.7%) and collegiate athletes (80.6%) (p<0.0001). Current HS (39.9%) and collegiate athletes (42.1%) recalled a statistically higher incidence of sport-related injury than current professional athletes (25.4%) (p<0.0001). Notably, only 22.33% of professional athletes said they would want their own child to specialize to play only one sport during childhood/adolescence. Conclusion: In our study, 46.3% of current high school athletes specialized to play only one sport. Additionally, high school athletes specialized, approximately two years earlier than collegiate and professional athletes surveyed This trend towards earlier sport specialization is concerning without evidence that early specialization provides any advantage for athletic advancement with potential predisposition towards higher injury risk.